A triple band hybrid MIMO rectangular dielectric resonator antenna for LTE applications - Cheh Lin, I.K. (Institute of Electrical and Electronics Engineers Inc., 2019)
In this paper, a triple band Multiple-Input Multiple-Output (MIMO) Rectangular Dielectric Resonator Antenna (RDRA) designed using hybrid techniques for Long Term Evolution (LTE) applications is investigated and presented. The proposed MIMO antenna can transmit and receive data independently by covering LTE Band 8 at 0.9 GHz, LTE Band 3 at 1.8 GHz, and LTE Band 40 at 2.3 GHz. Hybrid technique is adopted in this design by combining a meander line antenna with an RDRA to realize multiband operation. Meander line antenna has been proposed over the long vertical microstrip feeding line at 0.9 GHz, to employ a size reduction in the antenna, while two modes of RDRA are applied in this design: TE1δ 1y mode at 1.8 GHz and TE2δ 1y mode at 2.3 GHz. The proposed MIMO antenna has been fabricated and experimentally tested. The measured impedance bandwidths ( S11 <-10 dB) for the three stated bands are 4.40, 11.36, and 2.54 at Port 1, respectively and 5.47, 10.54, and 3.43 at Port 2, respectively. Measured isolations of-15.3 dB,-17.8 dB, and-47.0 dB are obtained at each described frequency, respectively. The performance of the proposed MIMO antenna is further validated using over-the-air LTE downlink throughput test. Throughputs of 93.16 Mbps, 93.01 Mbps, and 87.30 Mbps have been achieved for 0.9 GHz, 1.8 GHz, and 2.3 GHz, respectively, using 64 Quadrature Amplitude Modulation (QAM). In this regard, it is conceived that the proposed MIMO antenna can be a good candidate for LTE applications due to the validated excellent throughput performance. Â© 2013 IEEE.